2017
DOI: 10.4081/ijfs.2017.6177
|View full text |Cite
|
Sign up to set email alerts
|

Food safety and sustainable nutrition workshops: educational experiences for primary school children in Turin, Italy

Abstract: European control and prevention policies are focused to guarantee a high level of protection of consumers’ health. Food-borne diseases as obesity, diabetes, food allergy, and food-borne outbreaks are increasing. To prevent food-borne diseases, it is fundamental to involve consumers, in particular children, in educational experiences aimed to learn the proper behaviours to be applied. In this context, we designed and performed 5 educational workshops about food safety, hidden allergens in food and nutrition aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…All authors designed specifically tailored 40-90-minute workshops with the intention of promoting health and influencing the comprehension of preventive measures targeting food-related risks. The authors applied mostly cross-sectional pre-test/post-test surveys [10,32,33], with the exception of Traversa et al [34] who observed participants and their replies to the questions and practical activities proposed during the workshop. For evaluation purposes, only some of them applied control group and monitored short-term and long-term effects among the target population [10,33].…”
Section: Workhopsmentioning
confidence: 99%
See 2 more Smart Citations
“…All authors designed specifically tailored 40-90-minute workshops with the intention of promoting health and influencing the comprehension of preventive measures targeting food-related risks. The authors applied mostly cross-sectional pre-test/post-test surveys [10,32,33], with the exception of Traversa et al [34] who observed participants and their replies to the questions and practical activities proposed during the workshop. For evaluation purposes, only some of them applied control group and monitored short-term and long-term effects among the target population [10,33].…”
Section: Workhopsmentioning
confidence: 99%
“…Ovca et al [10] addressed the impact of temperature on microorganisms, the cleaning of kitchen gear, the removal of bacteria with hand washing, and the prevention of cross-contamination. Traversa et al [34] focused on characteristics and differences among microorganisms in the context of cooking, storage, and cross-contamination. Cross-contamination was also addressed in the case of allergens.…”
Section: Workhopsmentioning
confidence: 99%
See 1 more Smart Citation
“…These articles covered several ESC topics such as sustainable tourism, product lifecycle, energy conservation and efficiency, consumer education, packaging, carbon footprint and food (Chalfoun, 2014;Crawford, Luke, and Van Pelt, 2015;Danilane and Marzano, 2014;S. Gough and Scott, 1999;Hawas and Al-Habaibeh, 2017;Nowak et al, 2009;Oliver, 2016;Pankina et al, 2016;Traversa et al, 2017). Specifically in the waste education field, two articles addressed food waste, while the remaining articles addressed household waste, municipal solid waste, and solid waste in general (Çelikler and Harman, 2015;Davis, 2008;Finlayson, Gregory, Ludtke, Meoli, and Ryan, 2017;Maddox, Doran, Williams, and Kus, 2011;Painter et al, 2016;Redman, 2013;Zain et al, 2013).…”
Section: Type Of Education and Thematic Focusmentioning
confidence: 99%
“…Los niños que participan en experiencias educativas sobre seguridad alimentaria y nutrición tienen la oportunidad de aumentar su conciencia acerca de los comportamientos correctos para prevenir enfermedades transmitidas por los alimentos y mejorar su propio pensamiento crítico sobre el consumo de alimentos. 16 La seguridad alimentaria determina no sólo el estado de nutrición y salud actual de la población infantil, sino que condiciona su calidad de vida en la edad adulta y la mala nutrición de las generaciones futuras.…”
Section: Seguridad Alimentariaunclassified